A METHOD FOR ASSESSING HOUSEHOLD VULNERABILITY TO FLOOD AT REGENCIAL (KABUPATEN) LEVEL IN INDONESIA - Muriadi Muriadi; Andy Fefta Wijaya (Indonesian Journal of Environment and Sustainable Development, 2013)
A simplified method for assessing household vulnerability to flood in regencial level in Indoneisa is proposed in this paper. Two components of assessment proces is discussed, namely: Mapping the floods and its hazards and investigation of vulnerable elements and aspects. It is argued that complex flood mapping can be simplified using historical information on past flooding to develop a relation between probability of occurrence versus magnitude, and investigation of vulnerable households and aspects of their lives which can be carried out by in-depth interview or any relevant qualitative approaches. Flood hazards map can drawn based on flood types, while four aspects of household dimension namely food, housing, livelihood and health are focused in the investigation. Key words: vulnerability, assessment, flood-hazards, Indonesia